Transformasi Layanan Bimbingan Konseling Berbasis Digital Pasca-Pandemi: Pengaruh terhadap Karakter dan Prestasi Siswa - Triana, Dian (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2024)
This study aims to evaluate the impact of digital-based counseling services on students' character development and academic achievement in Jember Regency. Utilizing a descriptive quantitative method, the study involved 250 junior and senior high school students selected through stratified random sampling. The research instruments included the Emotional Intelligence Scale (EIS) to measure character development and the Academic Motivation Scale (AMS) to assess learning motivation and academic performance. The results revealed significant improvements in students' character dimensions, with empathy scoring the highest (4.3), followed by emotional regulation (4.1) and self-awareness (4.2). On the academic side, the students' average grades increased from 75.4 to 82.1, supported by a 16.7% increase in intrinsic motivation. The study also highlighted challenges such as technological infrastructure disparities in rural areas, affecting access to digital counseling services. This research concludes that digital-based counseling services effectively support holistic student development, both in character and academic achievement.